Strategi Pembrandingan Usaha Tahu di Desa Beligan: Analisis dan Implementasi - Zulkarnain, Zulkarnain; Pajama, Hanif Ubaidillah; Manurung, Jernih Natalia; Doriyanti, Agnees; Tinambunan, Cristine Laurencia; Matulatuwa, Angela Costansia Yohana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Branding strategy of tofu business in Beligan Village as an effort to improve the competitiveness and sustainability of micro, small, and medium enterprises (MSMEs) need to be considered. A qualitative analysis approach was taken to identify the challenges and opportunities faced by tofu businesses in marketing their products. Through in-depth interviews and observations, it was found that limited understanding of branding and marketing is a major obstacle. As a solution, it is suggested that implementation steps that include developing a strong brand identity, through the use of print media, social media and promotional videos need to be improved. The results of this study indicate that the implementation of appropriate branding strategies can increase the visibility of tofu products, expand market share, and ultimately empower tofu entrepreneurs of Beligan Village, Seberida District, Indragiri Hulu, Riau economically. This research is expected to be a reference for the development of MSMEs in other areas with similar potential.